2022
DOI: 10.3389/fonc.2022.967000
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SCAMP1 disrupts the balance between miR-26a-5p and ZEB2 to promote osteosarcoma cell viability and invasion

Abstract: Osteosarcoma often occurs in children and adolescents and affects their health. The survival rate of osteosarcoma patients is unsatisfactory due to the lack of early detection and metastasis development and drug resistance. Hence, dissection of molecular insight into osteosarcoma initiation and progression is pivotal to provide the new therapeutic strategy. In recent years, long noncoding RNAs (lncRNAs) have burst into stage in osteosarcoma development and malignant behaviors. LncRNA SCAMP1 has been discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Both pathways are involved in OS progression [ 15 , 16 ]. ZEB2 is involved in epithelial-mesenchymal transition (EMT) and may play a role in OS metastasis[ 17 ]. The roles of ZNF471, ALX4, and ZNF655 in OS are unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Both pathways are involved in OS progression [ 15 , 16 ]. ZEB2 is involved in epithelial-mesenchymal transition (EMT) and may play a role in OS metastasis[ 17 ]. The roles of ZNF471, ALX4, and ZNF655 in OS are unknown.…”
Section: Resultsmentioning
confidence: 99%
“…LncRNA EBLN3P regulated the expression of O-GlcNAc pathway via sponging miR-200a-3p, leading to methotrexate resistance in osteosarcoma cells 46 . Our previous study showed that lncRNA SCAMP1 regulated miR-26a-5p and ZEB2, contributing to promotion of cell invasion and viability in osteosarcoma 47 . These findings suggested that lncRNAs are involved in osteosarcoma development and progression.…”
Section: Discussionmentioning
confidence: 95%
“…1 µg of RNA was used to obtain cDNA via reverse transcription. PCR was performed by SYBR Green Kit as described before 47 . The expression of GAPDH was for normalization.…”
Section: Methodsmentioning
confidence: 99%
“…Secretory carrier membrane protein 1 (SCAMP1) is a lncRNA that promotes cancer progression through cell viability and invasion [75]. The SCAMP1 variant 2 (SCAMP1-TV2) shows increased expression in BC tumors from both LumA and TNBC subtypes and in several human BC cell lines, where SCAMP1-TV2 silencing promotes decreased levels of PI3K and AKT, both phosphorylated and unphosphorylated forms.…”
Section: Norad Higher In Low Cd8 T-cell Count; the Promotion Of Malig...mentioning
confidence: 99%